Retiring in a new age : life after paid work - Lansbury, Russell D.; Baird, Marian (Routledge, 2026)
This book examines the concept of retirement, how it has changed, and what the future holds for the next generation of retirees.The book analyses government data and university surveys of more than 1,000 retirees in Australia and 4,000 retirees in Sweden, as well as in-depth interviews with retirees in each country. It demonstrates that while both countries have differences in their retirement policies and practices, as well as the outcomes for retirees, the process of retirement is undergoing change in both countries as people retire at a range of ages, but often then re-enter the workforce for various reasons. The book proposes four distinctive post-retirement orientations: Stayers, Leavers, Blenders and Disengaged retirees. It then discusses how individuals, employers and governments are responding to the challenges of 'retiring in a new age', suggesting policies and a new social contract for retirees that addresses their needs for economic security, physical and mental health, as well as engagement with the wider community.A book of keen interest to scholars of employment and work relations, human resource management, as well as labour economics. Policymakers and students interested in employment issues that affect economic and social equality will also find the book's framework fit for use. A full set of interview transcripts and discussion questions is available on the Routledge webpage for download: www.routledge.com/9781041118329
Keywords: Retirement -- Sweden.; Retirement -- Australia.; elektronické knihy; electronic books